An eco-friendly synthesis of titanium oxide nanoparticles mediated from Syringodium isoetifolium and evaluate its biological activity and photocatalytic dye degradation - Velmani Sundar; Balamuralikrishnan Balasubramanian; Mani Sivakumar; Santhosh Chinnaraj; Vino Palani; Viji Maluventhen; Hesam Kamyab; Shreeshivadasan Chelliapan; Maruthupandian Arumugam; Diana Patricia Zuleta Mediavilla (Elsevier BV, 2024)
In this present investigation, titanium oxide nanoparticles (TiO2 NPs) were synthesized from seagrass aqueous extract of Syringodium isoetifolium. The TiO2 NPs were characterized by various spectroscopy techniques. The TiO2 NPs have a spherical shape, according to FE-SEM images. Then the TiO2 NPs exhibit antioxidant activities through DPPH (1, 1-diphenyl 2-picrylhyorazyl), 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) ABTS, and metal chelating assay. The DPPH and ABTS were better antioxidant activities compared to standard values. The investigation of antibacterial activity was against various microorganism, Staphylococcus epidermidis of the prime zone of inhibition was 18.6 mm and the anticancer activity against a human breast cancer cell line indicated excellent inhibition of cell viability; the IC50 value of 60 µg/mL shows dose-dependent specificity. Further, the TiO2 NPs were examined the methylene blue and methyl orange of dye degradation. The percentage of degradation by the TiO2 NPs was found to be higher in methylene blue (83 %) than methyl orange (58 %) for S. isoetifolium with marine macro algae extract after 120 min of visible light irradiation. The green synthesis of TiO2 NPs emphases to be cost effective and eco-friendly with antimicrobial and anti-cancer effects against breast cancer cell lines.
Keywords: Anticancer; Antioxidant; Dye degradation; Syringodium isoetifolium; TiO2 nanoparticle